Western visions of the Far East in a transpacific age, 1522-1657 - Lee, Christina H. (Transculturalisms, 1400-1700, 2012)
Introduction / Christina H. Lee -- "The Indies of the West" or, The tale of how an imaginary geography circumnavigated the globe / Ricardo Padrón -- Imagining China in a Golden Age Spanish epic / Christina H. Lee -- The first China hands : the forgotten Iberian origins of sinology / Liam Matthew Brockey -- Matteo Ricci on China via Samuel Purchas : faithful re-presentation / Nicholas Kos -- Representations of China and Europe in the writings of the Spanish Jesuit, Diego de Pantoja : accommodating the East or privileging the West? / Robert Richmond Ellis -- Women in the eyes of a Jesuit between the East Indies, New Spain, and early modern Europe / Haruko Nawata Ward -- Chinos in sixteenth century Spain / Juan Gil -- Native vassals : chinos, indigenous identity, and legal protection in early modern Spain / Tatiana Seijas -- Travelers from afar through civic spaces : the Tensho embassy in Renaissance Italy / Marco Musillo -- The Borghese papacy's reception of a samurai delegation and its fresco image at Palazzo del Quirinale, Rome / Mayu Fujikawa